PGSD STUDENTS’ PERCEPTION OF INFORMATION TECHNOLOGY INTEGRATION IN LEARNING - Dea Mustika; Yalvema Miaz; Yanti Fitria; Solfema; Hadiyanto; Nurhizrah Gistituati; Mega Iswari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses previous research studies that indicate the benefits and advantages of using information technology in learning. The research is to ascertain elementary school teacher education students' perceptions of integrating information technology in learning. The type of this research is qualitative survey research. The research was conducted in the elementary school teacher education study program of FKIP Riau through data collection techniques through questionnaires and interviews. The population in the study involved 72 elementary school teacher education study program students of FKIP Riau as a respondent in this research with a random sampling technique. The results of the analysis indicate that 81% of students had already knowledge about information technology, 77% indicates that they felt the benefits of information technology use, and 53% indicates they were satisfied with the integration of information technology in learning. Based on the conclusions of the research results, it is recommended that there should be variations in integrating information technology through various learning models or methods to make students experience more meaningful learning.